2019
DOI: 10.1016/j.soilbio.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas protegens CHA0 does not increase phosphorus uptake from 33P labeled synthetic hydroxyapatite by wheat grown on calcareous soil

Abstract: Please cite this article as: Meyer, G., Maurhofer, M., Frossard, E., Gamper, H.A., Mäder, P., Mészáros, É., Schönholzer-Mauclaire, L., Symanczik, S., Oberson, A., Pseudomonas protegens CHA0 does not increase phosphorus uptake from 33 P labeled synthetic hydroxyapatite by wheat grown on calcareous soil, Soil Biology and Biochemistry (2019), doi: https://doi. Abstract 18Soil microorganisms exuding organic acids have the potential to solubilize inorganic 19 phosphorus (P), which could improve the P availability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 67 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…The PSM-mediated bioavailable P is not utilized directly by plant or soil microbes; instead, it is quickly subject to precipitation or adsorption reactions in the immediate vicinity in which it is solubilized or desorbed by PSM [140]. Additionally, the P solubilization of exogenous PSM may be reduced due to the lack of persistence by competition with endogenous microbes for P resources, or by maladjustment of newly inoculated soil environment [141,142]. Hence, the PSM-enhanced P uptake from soil to plant likely occurs in the rhizosphere environment, which provides higher growth potential for PSM than bulk soils [74,142].…”
Section: Psm Enhance P Uptake From Soil To Plant In the Rhizosphere Ementioning
confidence: 99%
“…The PSM-mediated bioavailable P is not utilized directly by plant or soil microbes; instead, it is quickly subject to precipitation or adsorption reactions in the immediate vicinity in which it is solubilized or desorbed by PSM [140]. Additionally, the P solubilization of exogenous PSM may be reduced due to the lack of persistence by competition with endogenous microbes for P resources, or by maladjustment of newly inoculated soil environment [141,142]. Hence, the PSM-enhanced P uptake from soil to plant likely occurs in the rhizosphere environment, which provides higher growth potential for PSM than bulk soils [74,142].…”
Section: Psm Enhance P Uptake From Soil To Plant In the Rhizosphere Ementioning
confidence: 99%
“…New Phytologist (2021) 229: 1268-1277 Ó 2020 The Authors New Phytologist Ó 2020 New Phytologist Trust www.newphytologist.com However, few studies have shown that this mechanism is effective under field conditions (Karamanos et al, 2010;Leggett et al, 2015). Furthermore, microorganisms are unlikely to use energy to solubilise P if they do not need it themselves, especially in a soil environment under intense competition with other microorganisms (Meyer et al, 2019). Phosphate solubilisation by PSM in order to serve the plant is therefore questionable.…”
Section: Do Psm Solubilise P For Their Own Needs or For Plants?mentioning
confidence: 99%
“…However, their capacity to occupy specific ecological niches within the soil matrix, such as the rhizosphere, and subsequently function within these niches, remains important (Wakelin et al ., 2007). A lack of PSM performance on crop productivity and P uptake is often presumed to be related to poor soil colonisation due largely to competition with other microorganisms (Richardson, 2001; Meyer et al ., 2019; Raymond et al ., 2019a). Suppression of competition with native microbial communities, for example using sterilised soils, resulted in higher abundance and more positive effects of PSM on plant growth and P nutrition (Vassilev et al ., 2006; Pande et al ., 2017; Efthymiou et al ., 2018; Sarabia et al ., 2018).…”
Section: Factors Potentially Affecting Success or Failure Of Psm Inocmentioning
confidence: 99%
See 2 more Smart Citations